Plasma oxysterol levels in luminal subtype breast cancer patients are associated with clinical data - Kloudova-Spalenkova, Alzbeta; Ueng, Yune-Fang; Wei, Shouzou; Kopeckova, Katerina; Peter Guengerich, F; Soucek, Pavel (The Journal of steroid biochemistry and molecular biology, 2020)
Oxygenated metabolites of cholesterol (oxysterols) have been previously demonstrated to contribute to progression of various cancers and to modulate resistance to breast cancer endocrine therapy in vitro. We measured prognostic roles of circulating levels of seven major oxysterols in the progression of luminal subtype breast carcinoma. Liquid chromatography coupled with tandem mass spectrometry was used for determination of levels of non-esterified 25-hydroxycholesterol, 27-hydroxycholesterol, 7α-hydroxycholesterol, 7-ketocholesterol, cholesterol-5α,6α-epoxide, cholesterol-5β,6β-epoxide, and cholestane-3β,5α,6β-triol in plasma samples collected from patients (n = 58) before surgical removal of tumors. Oxysterol levels were then associated with clinical data of patients. All oxysterols except cholesterol-5α,6α-epoxide were detected in patient plasma samples. Circulating levels of 7α-hydroxycholesterol and 27-hydroxycholesterol were significantly lower in patients with small tumors (pT1) and cholesterol-5β,6β-epoxide and cholestane-3β,5α,6β-triol were lower in patients with stage IA disease compared to larger tumors or more advanced stages. Patients with higher than median cholestane-3β,5α,6β-triol levels had significantly worse disease-free survival than patients with lower levels (p = 0.037 for all patients and p = 0.015 for subgroup treated only with tamoxifen). In conclusion, this study shows, for the first time, that circulating levels of oxysterols, especially cholestane-3β,5α,6β-triol, may have prognostic roles in patients with luminal subtype breast cancer.
Keywords: nádorové biomarkery; Prognosis; invazivní růst nádoru; Biomarkers, Tumor; Neoplasm Invasiveness; Hydroxycholesterol; nádory prsu; Humans; Receptors, Estrogen; následné studie; lidé středního věku; Carcinoma, Ductal, Breast; Middle Aged; míra přežití; Receptors, Progesterone; Breast Neoplasms; receptory progesteronu; prognóza; Follow-Up Studies; Oxysterols; Receptor, ErbB-2; Breast cancer; Oxysterol; Plasma; duktální karcinom prsu; Survival Rate; receptor erbB-2; Cholestane-3β,5α,6β-triol; Cholesterol; oxysteroly; ženské pohlaví; receptory pro estrogeny; lidé; Female